Relation of study quality, concordance, take home message, funding, and impact in studies of influenza vaccines: systematic review. (12th February 2009) - Jefferson, T; Di Pietrantonj, C; Debalini, M G; Rivetti, A; Demicheli, V
Abstract : Objective To explore the relation between study concordance, take home message, funding, and dissemination of comparative studies assessing the effects of influenza vaccines. Design Systematic review without meta-analysis. Data extraction Search of the Cochrane Library, PubMed, Embase, and the web, without language restriction, for any studies comparing the effects of influenza vaccines against placebo or no intervention. Abstraction and assessment of quality of methods were carried out. Data synthesis We identified 259 primary studies (274 datasets). Higher quality studies were significantly more likely to show concordance between data presented and conclusions (odds ratio 16.35, 95% confidence interval 4.24 to 63.04) and less likely to favour effectiveness of vaccines (0.04, 0.02 to 0.09). Government funded studies were less likely to have conclusions favouring the vaccines (0.45, 0.26 to 0.90). A higher mean journal impact factor was associated with complete or partial industry funding compared with government or private funding and no funding (differences between means 5.04). Study size was not associated with concordance, content of take home message, funding, and study quality. Higher citation index factor was associated with partial or complete industry funding. This was sensitive to the exclusion from the analysis of studies with undeclared funding. Conclusion Publication in prestigious journals is associated with partial or total industry funding, and this association is not explained by study quality or size.